A szociológia egy sikeres évszázad után - Nemédi, Dénes (Szociológiai Szemle, 2024)
The paper deals with developments which in all probability, will have an influence on the future course of sociology: the growing uncertainty whether society as a distinct, and in most cases national, social system, the very object of sociology, exists; the quantitive expansion of university edication that transforms the traditional ways science operates; the dissolution of the classical intelligentsia which was the reluctant public o f sociological discourse. The concluding part of the paper discusses some recent proposals to deal with the emergent crisis.